Relaxation Behavior of Poly(ethylene terephthalate)/Poly(ethylene naphthalene 2,6-dicarboxylate) Blends Prepared by Cryogenic Blending - Denchev, Z. (2002)
A method including cryogenic grinding, melt pressing from the molten state, and quenching was used to prepare blends of poly(ethylene terephthalate) (PET) and poly(ethylene naphthalene 2,6-dicarboxylate) (PEN) in which the two phases were highly dispersed. The effect of melt-pressing times on the thermal properties and relaxation behavior of PET/PEN films were characterized with differential scanning calorimetry and dielectric spectroscopy. For short melt-pressing times, two glasstransition, two crystallization, and two melting peaks were observed, indicating the presence of PET-rich and PEN rich phases in these blends. Longer melt-pressing times revealed a single glass transition and a single _-relaxation process, showing that PET–PEN block copolymers were likely to be formed during the melt pressing. The experimental findings were examined in terms of the transesterification reactions between the blend components, as revealed by 1H NMR measurements.